Jenkins continuous integration cookbook : over 80 recipes to maintain, secure, communicate, test, build, and improve the software development process with Jenkins /: over 80 recipes to maintain, secure, communicate, test, build, and improve the software development process with Jenkins. (©2012) - Unknown
No abstract available